2016
DOI: 10.1093/asj/sjw183
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Implants in 2-Stage Breast Reconstruction: 9-Year Clinical Experience

Abstract: Radiation therapy increases the risk of high-grade CC with textured or smooth implants. PU implants are associated with a much lower cumulative incidence of CC following 2-stage breast reconstruction, even when radiotherapy is performed. LEVEL OF EVIDENCE 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
1
10
0
3
Order By: Relevance
“…Textured implants used were from Allergan (Natrelle™ 410, Allergan, Inc., Irvine, California) and Silimed (NUANCE 20646, Silimed, Rio de Janeiro, Brazil), and PU covered implants were from Polytech (Microthane®, POLYTECH Health & Aesthetics, Dieburg, Germany). PU implants were more intensively used since 2016, when it was reported an advantage performing breast reconstruction with PU implant [32,35,36].…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Textured implants used were from Allergan (Natrelle™ 410, Allergan, Inc., Irvine, California) and Silimed (NUANCE 20646, Silimed, Rio de Janeiro, Brazil), and PU covered implants were from Polytech (Microthane®, POLYTECH Health & Aesthetics, Dieburg, Germany). PU implants were more intensively used since 2016, when it was reported an advantage performing breast reconstruction with PU implant [32,35,36].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Thereafter, textured (TE) surfaces have been developed to mimic the shape and the benefits of the PU foam, and several studies have indicated that PU implants have a lower incidence of CC [17,26e36]. Furthermore, two studies have suggested that PU implants are associated with a lower incidence of CC in case PMRT is delivered [32,35].…”
Section: Introductionmentioning
confidence: 99%
“…Support for use of polyurethane implants for breast reconstruction in the setting of radiotherapy is based on level IV evidence only at the present time. However, reports show a trend towards lower rates of complications using polyurethane compared with silicone implants after radiotherapy. The role of fat grafting as an adjunct in breast reconstruction in either previously irradiated patients or those having PMRT, remains contentious and is based on case series showing favourable outcomes using fat grafting before the second stage of an implant‐based reconstruction.…”
Section: Resultsmentioning
confidence: 98%
“…Deflation-lipofilling sessions are conducted to prevent complications during the reconstructive step, limiting the onset of postoperative complications. As other authors promote the use of polyurethane implants as a first step in breast reconstruction to reduce complication rates [40,41] and not only as a rescue tool after a failure, in the same way, the present study investigated the beneficial effect of fat grafting as a part of the standard two-stage breast implant reconstruction for all postmastectomy patients in order to reduce overall capsular contracture and improve the esthetic result. This is the first report of 84 patients, a case-control study, with a mean follow-up time of 34.87 months.…”
Section: Discussionmentioning
confidence: 99%